Assessment of oral health status and treatment needs among TSRTC employees in Hyderabad City, Telangana, India - Patanapu, Siva Kumar; Arelli, Naresh; Veeraboina, Nagarani; Reddy, Kandadi Vasavi; Dantala, Satya Narayana; Voruganti, Sreenivas (International Journal Of Community Medicine And Public Health, 2022)
Background: The trend in all countries is industrialization; it leads to many occupational health problems and diseases among transport workers. The workers may be exposed to hazardous environment which affect the general as well as oral health because of the relative lesser importance given to it. The use of products related to tobacco and poor oral hygiene practices adds to the oral disease burden among this population. Methods: The study population consisted of 404 people, and oral health was examined using the World Health Organization (WHO) Oral Health Assessment form from 1997. Statistical Package for Social Sciences (SPSS) version 21.0 was used to analyze the data. The Chi-square test, t-test, and Analysis of Variance were used to compare study population proportions and mean scores (ANOVA). Results: The number of sextants influenced by CPI and LOA was found to be considerably larger (p=0.005) among guys who had completed high school education. Buccal mucosa showed ulcerations and leukoplakia from oral mucosal ulcers. Males aged 46-60 years old had significantly higher mean DMFT scores (3.31±4.44; 2.11±3.33 respectively) than females aged 46-60 years old (p=0.005). Overall, male workers aged 30-45 years old with a high school degree were shown to have a higher risk of acquiring oral health problems and requiring treatment. Conclusions: According to the findings, TSRTC personnel aged 30-45, males with a primary school education, had poor oral mucosal health and periodontal status. Workers with a high school education have a higher prevalence of dental caries and unmet dental care needs. As a result, there is an urgent need to focus on these high-risk groups.